EXPLORING THE RELATIONSHIP BETWEEN SELF-REGULATED LEARNING STRATEGIES AND COMPUTER PROGRAMMING ACHIEVEMENT IN HIGHER EDUCATION (Proceedings of the International Conference on Education, 2019)
This paper aims to report and discuss the findings of a research project exploring the relationship between self-regulated learning (SRL) strategies and computer programming achievement in higher education. In the project, data were collected from 66 undergraduate students who enrolled in a 13-week introductory computer programming course offered by a Hong Kong university during the academic year 2018/19. Participants were asked to complete the Motivated Strategies for Learning Questionnaire (MSLQ) to measure their use of SRL strategies. Their computer programming achievement was assessed by continuous exercises and the end-of-course examination as part of the course assessment. A quantitative correlational analysis on the questionnaire and assessment scores was conducted to explore the relationship between use of SRL strategies and computer programming achievement. The results of the project indicate that higher-order cognitive strategies, metacognitive control strategies, time and study environment strategies as well as help-seeking strategieswere positively associated with computer programming achievement. The findings suggest that students could be trained to use certain SRL strategies in order to effectively participate in computer programming activities.
Keywords: self-regulated learning strategies; computer programming; learning achievement